From Rab to Raab: The Construction of the Office of First Secretary of State. Issue 1 (14th June 2021) - Thornton, Stephen; Kirkup, Jonathan
Abstract: Through information gained from interviews with key political actors, archival research and close examination of biographical material, this article aims to provide the first detailed account of what it means to be the British First Secretary of State. Sometimes regarded simply as a synonym for Deputy Prime Minister, it will be demonstrated that the reality is far more complicated. Not all First Secretaries have been regarded as the Prime Minister's second-in-command, indeed there have been many years where the post has ceased to exist. Yet, at other times, First Secretaries have led the country, albeit briefly. The main argument to be made is that the office of First Secretary of State is only as important as the person holding that office is perceived to be important, but there is potential for that to change.